2001
DOI: 10.1177/0734242x0101900607
|View full text |Cite
|
Sign up to set email alerts
|

Co-combustion of shredder residues and municipal solid waste in a Swedish municipal solid waste incinerator

Abstract: Incinerating automotive shredder residue (ASR) in order to increase the recovery from end of life vehicles (ELVs) is an attractive option when recycling this material. In this study, incineration combined with energy recovery, was investigated. The incineration experiments, where 20% shredder residue (SR) was burnt with conventional municipal solid waste (MSW), were conducted in a full-scale MSW horizontal grate incinerator. Measurements were made before, during and after the incineration. The results showed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 9 publications
(10 reference statements)
1
10
0
Order By: Relevance
“…Also Aae Redin et al [9] and Börjeson et al [8] reported the lower concentration values for PCBs in ASR.…”
Section: Pop Concentrations In the Input Wastesmentioning
confidence: 96%
See 1 more Smart Citation
“…Also Aae Redin et al [9] and Börjeson et al [8] reported the lower concentration values for PCBs in ASR.…”
Section: Pop Concentrations In the Input Wastesmentioning
confidence: 96%
“…ASR is indeed known to contain high concentrations of PCDD/Fs, PCBs and also plasticizers such as di-2-ethylhexyl-phthalate (DEHP) [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Automotive shredder residue (ASR) is a waste stream known to contain high concentrations of PCDD/Fs, PCBs and also plasticizers such as di-2-ethylhexylphtalate (DEHP) [12][13][14][15]. ASR is the fraction that remains at the end of the end-oflife vehicle's (ELVs) dismantling and recycling process, typically consisting of dismantling of reusable and/or hazardous parts, shredding of the car hulk followed by mechanical recovery of metals and in some cases plastics.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, these persistent organic pollutants (POPs) are unintentionally formed in the incinerator and found in the output (Sakai et al, 1999;Abad et al, 2000;Sakai et al, 2001;Abad et al, 2002). The waste to be incinerated, however, also contains a range of POPs (Wilken et al, 1992;Mark et al, 1998;Sakai et al, 1998;Sakai et al, 1999; Aae Redin et al, 2001;Sakai et al, 2001;Vehlow et al, 2002;Tange and Drohmann, 2005;Ishikawa et al, 2007;Morf et al, 2007;Schlummer et al, 2007). It is generally assumed that the incoming POPs are destroyed during incineration and that during the cooling of the flue gases new PCDD/Fs and PCBs are formed through precursors or through de novo synthesis (Everaert and Baeyens, 2002;McKay, 2002).…”
Section: Introductionmentioning
confidence: 99%